2023
DOI: 10.3389/fcvm.2022.1037940
|View full text |Cite
|
Sign up to set email alerts
|

The association of the paraoxonase 1 Q192R polymorphism with coronary artery disease (CAD) and cardiometabolic risk factors in Iranian patients suspected of CAD

Abstract: IntroductionThe present study aimed to investigate the association of the paraoxonase 1 (PON1) Q192R polymorphism with coronary artery disease (CAD) and cardiometabolic risk factors in Iranian patients suspected of CAD.MethodsThis cross-sectional study was conducted on 428 patients undergoing angiography. The data related to demographic information and physical activity were collected by valid and reliable questionnaires. The PON-1 genotypes were detected by the polymerase chain reaction-restriction fragment l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Similarly, the PON1 enzyme is found in circulating high-density lipoprotein (HDL) particles [ 44 ]. The Q192R PON1 polymorphism and the ε4 allele are both implicated in modifying the risk of cardiovascular disease, secondary to their role in lipid metabolism [ 45 47 ]. Therefore, it is possible that environmental toxicants, by interacting with these genes, may have modified lipid metabolism pathways that contribute to the pathogenesis of GWI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the PON1 enzyme is found in circulating high-density lipoprotein (HDL) particles [ 44 ]. The Q192R PON1 polymorphism and the ε4 allele are both implicated in modifying the risk of cardiovascular disease, secondary to their role in lipid metabolism [ 45 47 ]. Therefore, it is possible that environmental toxicants, by interacting with these genes, may have modified lipid metabolism pathways that contribute to the pathogenesis of GWI.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the apolipoprotein E (apoE) protein is involved in lipid transport, and the ε4 allele lowers apoE availability within HDL particles. Since this PON1 polymorphism and the ε4 allele are both implicated in modifying the risk of cardiovascular disease, secondary to their role in lipid metabolism [42][43][44], it is, therefore, possible that environmental toxicants may modify lipid metabolism pathways that contribute to the pathogenesis of GWI. In that regard, our prior studies have shown increased triglycerides in the blood of veterans with GWI [30].…”
Section: Discussionmentioning
confidence: 99%